Variation in models for simple dynamic structure–soil–structure interaction problems. (2017) - Andersen, L.V.; Peplow, A.; Bucinskas, P.; Persson, P.; Persson, K.
Abstract: To account for dynamic cross-coupling of structures via the soil, a computational model must be accurate enough to provide the correct overall behaviour of the scattered wave field. However, simplicity is also important when a model should be used for design purposes, especially in the early design stages and feasibility studies. The paper addresses the accuracy of simple models in which an array of structures is simplified into blocks placed on the ground surface or embedded within the soil. Comparisons are made between models that account or do not account, in a proper manner, for the inertia and embedment of the structures. Especially, the limitations of simplified models are discussed regarding their capability to quantify the insertion loss accurately.